ANALISIS MOTIF BERBELANJA DI HYPERMART PANAKKUKANG MAKASSAR - abdin abdin (AkMen JURNAL ILMIAH, 2008)
This research was aimed to knowing the motiffs which influence the constumer’s to purchase at Hypermart Panakkukang Makassar. Beside, it was aimed to finding out the dominant motiff which influences the constumer’s to purchase at Hypermart Panakkukang Makassar. Based on research result and data analyse,it was find that statiscally, by using multiple linear regresion method, the goods price and the goods variety gave strong influences of the consumer’s to purchse at hypermart panakkukang Makassar. Among the consumer’s influencing motiffs to purchase at Hypermart Panakkukang Makassar, the most dominant is the goods prince